2021
DOI: 10.1038/s41467-021-25720-2
|View full text |Cite
|
Sign up to set email alerts
|

High resolution global spatiotemporal assessment of rooftop solar photovoltaics potential for renewable electricity generation

Abstract: Rooftop solar photovoltaics currently account for 40% of the global solar photovoltaics installed capacity and one-fourth of the total renewable capacity additions in 2018. Yet, only limited information is available on its global potential and associated costs at a high spatiotemporal resolution. Here, we present a high-resolution global assessment of rooftop solar photovoltaics potential using big data, machine learning and geospatial analysis. We analyse 130 million km2 of global land surface area to demarca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 58 publications
(57 reference statements)
1
58
0
Order By: Relevance
“…Reference [35] presented an assessment of the potential of solar rooftop photovoltaics using big data machine learning and geospatial analysis. Their results showed that the cost of attaining the potential is lowest in India (66$MWh −1 ) and China (68$MWh −1 ), with the USA (238$MWh −1 ) and UK (251$MWh −1 ) representing some of the costliest countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reference [35] presented an assessment of the potential of solar rooftop photovoltaics using big data machine learning and geospatial analysis. Their results showed that the cost of attaining the potential is lowest in India (66$MWh −1 ) and China (68$MWh −1 ), with the USA (238$MWh −1 ) and UK (251$MWh −1 ) representing some of the costliest countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…where CVaR for a random variable is defined in (1). If W has a smooth cumulative distribution function, the above constraint imposes that the probability of violating the upper bound on voltage magnitudes is bounded above by 1 − ν and the expectation of W − W over its ν-tail is bounded above by zero.…”
Section: Cvar-sensitive Hca Problemsmentioning
confidence: 99%
“…The feasible set for this dual problem is a convex cone. 1 Call the objective function of this problem as D(λ, µ, µ 1 , µ 2 ; ψ). Then, for any feasible λ…”
Section: An Incremental Algorithm To Solve a C (ψ)mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Globally, it has been estimated that there is 27 PWh yr -1 of rooftop electricity generation potential. 6 Research on new photovoltaic concepts 7 can open up pathways to the efficiency regime beyond the detailed-balance "barrier," enabling even more solar energy potential with less area, rooftop or land, required, and therefore less ecological and other impact. To that end, we invite submissions to our special section on Novel Photovoltaic Device Architectures, 8 which will showcase new device architectures, materials, and photon management strategies to help propel the field into a new era of high-efficiency devices.…”
mentioning
confidence: 99%